Integrating Local Wisdom and Modern Education: A Holistic Approach to Curriculum Development - Homsombat, Phitsanu (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper explores the integration of local wisdom with modern education to develop a holistic approach to curriculum design. The blending of indigenous knowledge with contemporary pedagogical methods enhances students’ academic performance, cultural identity, and community engagement. By examining case studies from various educational institutions, this study highlights the benefits of incorporating local traditions, ethical values, and reflective practices into formal learning environments. The research discusses key challenges, including teacher preparedness, resource availability, and the need for policy adjustments to support culturally responsive education. Furthermore, the paper emphasizes the role of interdisciplinary collaboration in fostering inclusive and adaptive learning models. The findings suggest that a balanced educational framework that respects both traditional and modern knowledge can create a sustainable and meaningful learning experience. This study contributes to ongoing discussions on curriculum development by advocating for a culturally grounded yet globally relevant approach to education.